Business Agile Model for Startups in the Meat Industry using Digital Marketing, Lean Canvas and Lean Startup - Gutierrez Posadas, Alexandro Manuel (2023)
The following research focuses on the implementation of a business model for startup projects in the meat industry, using agile methodologies such as Lean Canvas, Lean Startup, Digital Marketing and Agile, to be used by entrepreneurs in the Peruvian meat business market. The proposed business model is important to be used as a digital tool for Peruvian entrepreneurs to achieve their commercial and productive objectives, using the most updated digital tools in the current industry which also would provide them the capacity to adapt to different scenarios in the flexible market in which they are involved. Also, the following scientific article shows information about characteristics of the market of study, economic, financial, and social evaluation that will be related to this investigation. In the same way, previous studies of similar topics would be incorporated in the following research, using their contribution to find solutions for common problems of small and medium entrepreneurs in the Peruvian market. Finally, using a simulator software, we could have special indicators that would support the effectiveness of the following research and the magnitude of the contribution of this research to future investigations.